An integrated pest and pollinator management approach for smallholder avocado (Persea americana Mill.) farms under different landscape contexts - Yusuf, Abdullahi Ahmed (University of Pretoria, 2021)
Thesis (PhD (Entomology))--University of Pretoria, 2021.